Prevalence and associated factors of domestic violence against married rural women of Gurugram, Haryana - ., Shambhavi; Deswal, Balbir Singh; Ray, Shalini; Singh, Manisha (International Journal Of Community Medicine And Public Health, 2019)
Background: The global health burden from domestic violence against women in reproductive age group is about 9.5 million disability adjusted life years (DALYs). Women suffering from violence have more chances of suffering from physical, emotional, and mental problems such as anxiety, depression and post-traumatic stress disorder. The objectives of the present study are to find the prevalence and awareness of domestic violence in an urban slum of Gurugram and to elicit associated risk factors and the reasons for tolerance of domestic violence. Methods: A community based, cross sectional study was conducted among married women (18-45 years) using a semi structured questionnaire in a rural area of Gurugram by systematic random sampling. Sample size collected was 900. Study population was enquired about the awareness regarding domestic violence, self-experience about domestic violence and about the form of violence experienced and the reasons for their tolerance. Data was entered and analyzed using Epi Info ver 7. Results: Total 980 subjects were enquired about their awareness and self-experience of domestic violence. Overall prevalence of domestic violence in the study population was 28%. Prevalence of domestic violence was statistically significantly associated with education, employment, duration of marriage (p value <0.05).The prevalence was highest of emotional violence (40.5%), followed by physical (33.4%), economic (21.4%) and sexual violence (4.7%). Conclusions: Public health professionals should emphasis on measures to raise public awareness so that women can talk freely about domestic violence and its consequences and help in mitigating this medico-social problem.